FEATURES OF THE INTERACTION BETWEEN LOCAL GOVERNMENT BODIES AND LAW ENFORCEMENT AUTHORITIES UNDER THE MARTIAL LAW CONDITIONS - Pryvarskyi, Yurii (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
Purpose: to outline the specifics of the interaction of local self-government bodies and law enforcement bodies under martial law conditions, in particular in the part of the legal regulation of the corresponding interaction, with the further aim of forming proposals for improving such regulation. Research methods: the theoretical nature of the proposed study determined the methodological apparatus that was used in the work - first of all, we mean general theoretical and analytical methods in combination with systemic and complex approaches. Results: the conducted analysis proves that the existing legal framework of the relevant cooperation is imperfect and has a general (unspecified) nature. Even for peacetime conditions, the legislator did not give definitions regarding the content (and form) of interaction between local self-government bodies and law enforcement authorities. With regard to the conditions of martial law, the current Law of Ukraine «On the Legal Regime of Martial Law» does not address the issue of granting local self-government bodies the authority to ensure public and state security, and the specified law does not contain norms defining the principles of interaction of local self-government with law enforcement authorities in conditions martial law. Discussion: the thesis is supported that the systematic, diverse forms and permanent interaction of local self-government and law enforcement authorities is a guarantee of effective activities to ensure public order and effective fight against crime. The situation in the conditions of martial law becomes even more acute, because the corresponding interaction is part of the protection of national security, in particular, public and state security. It is possible to change the relevant situation by creating a well-thought-out and effective legislative framework for the interaction of self-government with law enforcement bodies, particularly in martial conditions.